Efektivitas Penerapan Protection Motivation Theory (PMT) Sebagai Formula Mengatasi Adiksi Perokok Aktif - Huda, Miftahul; Najih, Ahmad Abi; Slamet, Slamet (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2023)
Active smoking addiction is a persistent global health problem with serious impacts on society. Cigarettes cause more than 8 million deaths each year, and around 7 million of them are victims of exposure to passive cigarette smoke. The importance of overcoming active smoking addiction encourages research and development of various prevention strategies. One approach that has attracted attention is the application of Protection Motivation Theory (PMT). This study uses a qualitative method with a descriptive approach. This research includes library research, with the aim of collecting data and information from various sources available in the library. These sources include books, magazines, documents, historical records, and others. Data collected from library research can be used as the basis and main source for field research. Library research is a type of research that examines secondary data. PMT as an effective formula in overcoming active smoker addiction, continuous evaluation and further research is needed. This will provide in-depth insight into the extent to which this theory can be applied in various contexts and help adapt prevention strategies to meet the unique needs of individuals as well as diverse societies. A deeper understanding of the effectiveness of PMT will provide a valuable contribution. The application of Protection Motivation Theory as a formula to overcome active smoking addiction shows significant potential in increasing awareness, changing attitudes, and stimulating intentions to quit smoking. However, it is important to continually adapt this approach to individual characteristics and changing social dynamics. Continuous evaluation and further research are needed to ensure its sustainability and effectiveness in addressing the challenges of active smoker addiction.